Investigation of the solubility of protoporphyrin IX in aqueous and hydroalcoholic solvent systems - Michelly de Sá Matsuoka; Giovanna Carla Cadini Ruiz; Marcos Luciano Bruschi; Jéssica Bassi da Silva (Beilstein Journal of Nanotechnology, 2025)
Photodynamic therapy (PDT) is a non-invasive treatment involving a photosensitizer (PS), light source, and tissue oxygen. Protoporphyrin IX (PpIX) is commonly used as a PS due to its tumor-targeting properties and phototoxicity. However, the physicochemical properties of PpIX foster self-aggregation, which is a challenge for its incorporation into pharmaceutical formulations. This study aimed to evaluate the solubility of PpIX in distinct solvent systems to support the development of novel pharmaceutical formulations. The shake-flask method was employed, using purified water, 50% ethanol (EtOH50), 77% ethanol (EtOH77), absolute ethanol (EtOHabs), and polymeric systems containing 10% (w/w) poloxamer 407 (P407) in water, in EtOH50 or in EtOH77. Approximately 10 to 25 mg of PpIX was added to 25 mL of the solvent, and the solutions were stirred at 100 rpm, at 37 °C, for up to 96 h. The PpIX concentration was measured by using a validated method (R = 0.9973), with equilibrium reached within 30 min. The dissolution profiles of the micellar systems were also evaluated using the Korsmeyer–Peppas model with lag time (tlag), which indicated a Fickian diffusion mechanism, preceded by a thermodynamically driven accommodation stage of PpIX into the micelles. The solubility of PpIX ranged from 0.138 mg/mL in water to 0.593 mg/mL in water containing 10% (w/w) P407. The solubility of PpIX in EtOH50 and EtOH77 with 10% (w/w) P407 was 0.503 and 0.507 mg/mL, respectively, while EtOHabs yielded the lowest solubility among ethanolic solvents (0.179 mg/mL). These results indicate that water and EtOHabs are unsuitable solvents for PpIX, whereas the nanostructured systems containing P407 showed the greatest potential for future pharmaceutical applications, mainly the aqueous one because of its low toxicity considering topical preparations.